Advanced tomography techniques for inorganic, organic, and biological materials. (7th July 2016) - Evans, James E.; Friedrich, Heiner
Abstract: Abstract : Three-dimensional (3D) tomography using electrons and x-rays has pushed and expanded our understanding of the micro- and nanoscale spatial organization of inorganic, organic, and biological materials. While a significant impact on the field of materials science has already been realized from tomography applications, new advanced methods are quickly expanding the versatility of this approach to better link structure, composition, and function of complex 3D assemblies across multiple scales. In this article, we highlight several frontiers where new developments in tomography are empowering new science across biology, chemistry, and physics. The five articles that appear in this issue of MRS Bulletin describe some of these latest developments in detail, including analytical electron tomography, atomic resolution electron tomography, advanced recording schemes in scanning transmission electron microscopy (STEM) tomography, cryo-STEM tomography of whole cells, and multiscale correlative tomography.